2004
DOI: 10.1038/sj.cdd.4401433
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism for the proapoptotic activity of ursodeoxycholic acid: effects on Bcl-2 conformation

Abstract: Ursodeoxycholic acid (UDCA), a relatively nontoxic bile acid, enhanced the apoptotic response of tumor cells to both photosensitizers that cause photodamage to Bcl-2 and to the nonpeptidic Bcl-2/Bcl-x L antagonist HA14-1. The latter agent binds to the surface pocket formed by the BH1, BH2 and BH3 domains of Bcl-2 and Bcl-x L . Fluorescence polarization studies indicated that affinity of HA14-1 for Bcl-2 was enhanced in the presence of UDCA. Moreover, Bcl-2 photodamage was promoted by UDCA using a photosensitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…This occurred in both L1210 mouse leukemia and 1c1c7 mouse hepatoma cells, using either SnET2 or CPO as the photosensitizing agent. The mechanism derived from a UDCA-induced conformational change in the Bcl-2 protein promoting affinity for the photosensitizer and thereby increasing Bcl-2 photodamage [11]. UDCA also enhanced binding to Bcl-2 by the small-molecule non-peptidic Bcl-2 antagonist HA14-1, initially described by Huang's group [12].…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
See 1 more Smart Citation
“…This occurred in both L1210 mouse leukemia and 1c1c7 mouse hepatoma cells, using either SnET2 or CPO as the photosensitizing agent. The mechanism derived from a UDCA-induced conformational change in the Bcl-2 protein promoting affinity for the photosensitizer and thereby increasing Bcl-2 photodamage [11]. UDCA also enhanced binding to Bcl-2 by the small-molecule non-peptidic Bcl-2 antagonist HA14-1, initially described by Huang's group [12].…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
“…A persisting question relating to PDT targets was the apparent resistance of the Bcl-2 analog Bcl-x L to photodamage in L1210 murine leukemia cells in suspension culture [11]. In contrast, Oleinick's group had found that Bcl-x L was as sensitive as Bcl-2 to photodamage in adhering cells [14].…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
“…This substrate releases the fluorescent dye Rhodamine 110 upon enzymatic hydrolysis. The increase in fluorescence as a function of time was measured with a Fluoreskan fluorescence plate reader using 485 nm excitation and 510 nm emission.Western blots for Bcl-2, phosphorylated and non-phosphorylated eIF2α, and LC-3Cells were lysed and extracts prepared for Western blot analysis [9]. Phosphatase inhibitors (5 mM NaF, 10 mM Na 4 P 2 O 7 , and 5 mM Na 3 VO 4 ) were present during extraction procedures.…”
mentioning
confidence: 99%
“…2E). These results are consistent with the proposal that salubrinal protects Bcl-2 from photodamage.A possible mechanism for the latter effect was provided by FRET analysis, using a procedure we had previously adopted for assessing the affinity of CPO for the Bcl-2 protein in a lysosomal environment [9]. Excitation of CPO at 400 nm leads to fluorescence at 642 nm, but excitation at 280 nm does not result in any detectable fluorescence emission (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation